2011
DOI: 10.1107/s0907444911015605
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution X-ray structure of the rabbit histidine triad nucleotide-binding protein 1 (rHINT1)–adenosine complex at 1.10 Å resolution

Abstract: Histidine triad nucleotide-binding protein 1 (HINT1) represents the most ancient and widespread branch in the histidine-triad protein superfamily. HINT1 plays an important role in various biological processes and has been found in many species. Here, the first complete structure of the rabbit HINT1-adenosine complex is reported at 1.10 Å resolution, which is one of the highest resolutions obtained for a HINT1 structure. The final structure has an R(cryst) of 14.25% (R(free) = 16.77%) and the model exhibits goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…At ambient temperature, most crystallization conditions produced needles. After 1-2 months, the growth of additional crystals with a tetragonal bipyramid shape, identical to previously obtained rHINT1 crystals (Dolot et al, 2011), was observed in the same drops. Crystallization at lower temperature using conditions consisting of 19%(w/v) PEG 8000, 100 mM sodium cacodylate pH 5.5 allowed crystals of a new crystal form with a plate shape and typical dimensions of 0.8 Â 0.4 Â 0.1 mm to be obtained.…”
Section: Cloning Expression Purification and Crystallization Of Hhint1supporting
confidence: 85%
See 1 more Smart Citation
“…At ambient temperature, most crystallization conditions produced needles. After 1-2 months, the growth of additional crystals with a tetragonal bipyramid shape, identical to previously obtained rHINT1 crystals (Dolot et al, 2011), was observed in the same drops. Crystallization at lower temperature using conditions consisting of 19%(w/v) PEG 8000, 100 mM sodium cacodylate pH 5.5 allowed crystals of a new crystal form with a plate shape and typical dimensions of 0.8 Â 0.4 Â 0.1 mm to be obtained.…”
Section: Cloning Expression Purification and Crystallization Of Hhint1supporting
confidence: 85%
“…Finally, the 'HINT' name was coined after structural analysis performed by Brenner et al (1997). At present, 14 HINT1 structures are available in the PDB: six human (Lima et al, 1996(Lima et al, , 1997, six rabbit (Brenner et al, 1997;Krakowiak et al, 2004;Dolot et al, 2011) and two from Escherichia coli (Bardaweel et al, 2010). The deposited structures display HINT in the apo state (Lima et al, 1996) or in complex with selected ligands: substrate analogues or products of their hydrolysis (Lima et al, 1997;Krakowiak et al, 2004;Bardaweel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The name "HINT" resulted from structural analysis [29]. Currently, many HINT1 structures are deposited in the PDB, including human [26,[30][31][32], rabbit [29,33,34], and bacterial homologs [8][9][10]. The deposited structures show HINT either in the apo state [26] or as complexes with selected ligands-either substrate analogs or products of their hydrolysis [8,30,33].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc is coordinated by these cysteine residues as well as the first histidine residue of the conserved triad motif (Lima et al, 1996). Structural and functional studies of human and rabbit HINT1 revealed that this protein is involved in regulation of transcription and is a potential tumour suppressor controlling regulation of the cell cycle (Maize et al, 2013;Dolot et al, 2011). While HINT and PKCI are functionally different, many key structural features of HINT have been found to be very similar to those of PKCI, pointing towards a common evolutionary origin for both.…”
Section: Introductionmentioning
confidence: 99%